Third Culture Teacher 2019 - Bailey, Lucy (John Catt Educational, 2019)
Dr Lucy Bailey presents a concise and coherent guide for those who are interested in pursuing a teaching career internationally. This book covers all the things you should consider as well as the advantages and disadvantages of living and working in an entirely new culture and country that you might face.